Detection of OXA-48-like and NDM carbapenemases producing Klebsiella pneumoniae in Jordan: A pilot study - Amin A. Aqel; Panagiota Giakkoupi; Hamed Alzoubi; Ibrahim Masalha; Matthew J. Ellington; Alkiviadis Vatopoulos (Elsevier, 2017)
Summary: Little is known of carbapenemase producing Klebsiella pneumoniae (CPK) in Jordan. This study aimed to determine the prevalence of CPK in a major hospital in Amman, Jordan in 2012-2013 and to characterize the isolates and detect the types of carbapenemase(s) they produced.For the 296 isolates investigated, species identification and antimicrobial susceptibilities were determined (Vitek II, bioMérieux). Isolates with decreased ertapenem susceptibility were tested for carbapenemase production using the Modified Hodge Test. Isolates with a carbapenemase-positive phenotype were characterized further via multiplex PCRs for extended-spectrum β-lactamase and carbapenemase genes and by Pulsed Field Gel Electrophoresis (PFGE).Seven of 296 K. pneumoniae isolated in 2012-2013 (2.4%) were carbapenemase producers, five produced class D carbapenemases (OXA-48-like) and two produced a NDM metallo-beta-lactamase. All seven isolates also encoded CTX-M enzymes; CTX-M-1-like enzymes were detected in five isolates (two co-producing NDM enzymes and three co-producing OXA-48-like enzymes), CTX-M-9 was found in the two remaining OXA-48-like producers. PFGE revealed five genetically distinct types amongst the seven carbapenemase producing K. pneumoniae, with two pairs of identical isolates associated with patients treated on the same wards.The emergence of OXA-48-like and NDM carbapenemases associated with multi-drug resistant (MDR) isolates in Jordan is concerning. The strict implementation of infection control practices will help to disrupt the spread of MDR carbapenemase producers in Jordanian hospitals. Keywords: Carbapenemase, CTX-M, NDM, OXA-48-like, K. pneumoniae, Jordan